Flexural strength of FRP plated RC beams using a partial-interaction displacement-based approach - Mohamed El-Zeadani; M. R., Raizal Saifulnaz; Y. H., Mugahed Amran; Hejazi, F.; Jaafar, M. S.; Alyousef, Rayed; Alabduljabbar, Hisham (Elsevier, 2019)
esigning FRP plated RC beams using full-interaction moment-curvature analysis would often suggest that the RC structure is brittle with debonding often occurring prior to yielding of the reinforcement steel. For that reason, researchers have looked into a displacement-based approach that takes into account the member debonding mechanism. The force in the plate within the debonded region was assumed to remain at the intermediate crack debonding force, PIC, and the ultimate strength was determined by considering compatibility of displacements along the member length. However, from laboratory testing, it is seen that the force in the externally bonded FRP plate keeps building up until failure occurs. Therefore, in this study, an extension to the displacement-based approach developed by previous researchers for FRP plated beams is presented where the residual bondstress of the plate within the debonded region is incorporated in the analysis. This is achieved by adopting a bond-slip model with a residual shear component that allows for the force in the plate to increase beyond PIC. The ultimate strength of the FRP plated beams is determined when the plate displacement matches that of the concrete near the plate end. A comparison with the experimental results of seven adhesively plated beams shows that incorporating the residual bondstress of the externally bonded plate yields significant improvement in accuracy and give better correlation with experimental findings.